2007
DOI: 10.5380/cep.v25i1.8404
|View full text |Cite
|
Sign up to set email alerts
|

QUALIDADE DO MEXILHÃO <i> Perna perna </i> SUBMETIDO AO PROCESSO COMBINADO DE COCÇÃO, CONGELAMENTO E ARMAZENAMENTO

Abstract: Mexilhões da espécie Perna perna, cultivados e comercializados no município de Ubatuba (SP), foram submetidos ao processamento por cocção, congelamento e armazenamento. Foram determinados o ponto de congelamento, a velocidade de congelamento a as curvas de congelamento do mexilhão semi-desconchado, sendo também avaliada a qualidade microbiológica e físico-química do produto. O beneficiamento do mexilhão iniciou-se com a cocção por imersão em água a ebulição por 10 min (permitindo a retirada das conchas), sendo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
2
1

Year Published

2014
2014
2021
2021

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 25 publications
0
2
1
Order By: Relevance
“…The moisture (74.74%) and ash (1.52%) contents detected in P. perna mussel species were lower than those found by Furlan, Galvão, Salan, and Oetterer (2007) and Cordeiro, Lopes, Oetterer, Porto, and Galvão (2007), of 83.8 and 85% for moisture and 1.8 and 3.8% for ash, respectively. Conversely, the crude protein (18.42%) and total lipids (4.07%) were higher than those verified by these same previous studies, which reported a corresponding 9.1 and 7.2% for protein and 1.1 and 1.1% for lipids, respectively.…”
Section: Centesimal Compositioncontrasting
confidence: 58%
“…The moisture (74.74%) and ash (1.52%) contents detected in P. perna mussel species were lower than those found by Furlan, Galvão, Salan, and Oetterer (2007) and Cordeiro, Lopes, Oetterer, Porto, and Galvão (2007), of 83.8 and 85% for moisture and 1.8 and 3.8% for ash, respectively. Conversely, the crude protein (18.42%) and total lipids (4.07%) were higher than those verified by these same previous studies, which reported a corresponding 9.1 and 7.2% for protein and 1.1 and 1.1% for lipids, respectively.…”
Section: Centesimal Compositioncontrasting
confidence: 58%
“…Since feed in this case does not undergo freezing, the formation of ice crystals can be prevented. As noted previously, this condition can cause tissue damage, and such damage, in turn, can result in exudation, loss of liquids, reduction of nutritional value, and change of the texture and appearance of feed (Cordeiro et al, 2007). Additionally, feed stored at 4°C reduces energy cost compared to that stored at -18°C.…”
Section: Resultsmentioning
confidence: 93%
“…However, freezing forms ice crystals which can cause tissue damage. This process results in exudation, fluid loss, reduced nutritional value, and changes in the texture and appearance of feed after defrosting (Cordeiro et al, 2007). Freezing can also affect the structural and chemical properties of meat, such as muscle fibers, lipids and proteins (Pietrasik & Janz, 2009).…”
Section: Introductionmentioning
confidence: 99%